2016
DOI: 10.1080/2162402x.2015.1134412
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of CD8 to Treg tumor-infiltrating lymphocytes is associated with response to cisplatin-based neoadjuvant chemotherapy in patients with muscle invasive urothelial carcinoma of the bladder

Abstract: Introduction: Randomized controlled trials of platinum-based neoadjuvant chemotherapy (NAC) for bladder cancer have shown that patients who achieve a pathologic response to NAC exhibit 5 y survival rates of approximately 80–90% while NAC resistant (NR) cases exhibit 5 y survival rates of approximately 30–40%. These findings highlight the need to predict who will benefit from conventional NAC and the need for plausible alternatives. Methods: The pre-treatment biopsy tissues from a cohort of 41 patients with mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 42 publications
(32 reference statements)
10
118
0
1
Order By: Relevance
“…Our findings support prior studies suggesting that bladder tumor development and treatment response is characterized by changes in effector to regulatory T-cell ratios (25, 26). We also found that BCG leads to a substantial recruitment of CD4 + T cells and an increase in the CD4 + /FoxP3 + ratio, confirming prior work from the early 1990s that identified via IHC an influx of CD4 + cells in BCG treated patients (6, 7).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings support prior studies suggesting that bladder tumor development and treatment response is characterized by changes in effector to regulatory T-cell ratios (25, 26). We also found that BCG leads to a substantial recruitment of CD4 + T cells and an increase in the CD4 + /FoxP3 + ratio, confirming prior work from the early 1990s that identified via IHC an influx of CD4 + cells in BCG treated patients (6, 7).…”
Section: Discussionsupporting
confidence: 92%
“…The hypothesis that the immune system also plays a role in the response of urothelial carcinoma to systemic chemotherapy is supported by a recent study by Baras et al, in which ratio of CD8 + TILs to CD25 + T regs was strongly associated with response to platinum-based neoadjuvant chemotherapy [268]. As mentioned above, it appears that in urothelial carcinoma the expression of checkpoint molecule PD-L1 on the cells of the immune infiltrate is more relevant in predicting response to PD-1 and PD-L1 inhibitors than expression on tumor cells [250,251].…”
Section: Tils In Genitourinary Carcinomasmentioning
confidence: 97%
“…115 Tumor cell PDL1 expression is observed in ~20% of muscle invasive urothelial carcinomas. 114,116 Increased tumor cell PD-L1 expression is generally associated with higher-stage disease, but an association with postcystectomy survival has not been consistently observed across multiple cohorts. 114,117122 Many of the observed differences between these studies may be attributable to the use of different PD-L1 immunohistochemistry protocols, antibodies, scoring criteria, and sample sizes—again highlighting the perils of trying to compare across studies when there is a lack of assay harmonization and a unified scoring approach.…”
Section: Urothelial Carcinomamentioning
confidence: 99%
“…Notably, the immune contexture is also predictive of response to non-immune-based therapies such as conventional platinum-based neoadjuvant chemotherapy, whereby an increasing ratio of Treg to CD8 density is predictive of residual muscleinvasive tumor posttreatment. 116 …”
Section: Urothelial Carcinomamentioning
confidence: 99%